Role of international price and domestic inflation in triggering export restrictions on food commodities - Mamun, Abdullah; Laborde Debucquet, David (Wiley, 2025)
This paper investigates the drivers of export restrictions on agricultural products based on an original dataset developed at IFPRI. We focus on four food price crises when export restrictions (bans, taxes, licenses, etc.) were applied: the 2007–2008 and 2010–2011 food price crises, the COVID‐19 pandemic, and the 2022 crisis associated with the Russia–Ukraine war. Although the justifications for such trade policies have been discussed in the literature, the ability to forecast their implementation remains understudied. The probit model used in this study suggests that the inflation rate has a higher power to predict export restrictions than do international commodity prices. The probability of export restrictions increases more when price changes are measured from a reference level in the long term than in the short term. Among the covariates, agricultural land per capita, the commodity's share in total production, and weather conditions increase the chances of imposing export restrictions. Population density, share of agriculture in GDP, urbanization rate, and political economy indicators all have a negative influence on the likelihood of export controls.